Ammonia and nitrous oxide emissions of a stoichiometric natural gas engine operating with high caloric value and low caloric value fuels. (1st February 2021) - Li, Menghan; Tian, Hongjian; Wei, Zhangning; Zhang, Qiang; Shen, Boxiong
Highlights: NH3 and N2 O emissions were investigated at both steady and transient conditions. NH3 and N2 O are high when using high caloric value fuel during steady test cycle. N2 O emissions are mainly emitted during the engine cold starting process. N2 O emissions of low caloric fuel are higher in cold WHTC while lower in hot WHTC. Abstract: With the implement of the increasingly stringent emission standards, natural gas engines feature stoichiometric operation with three way catalyst (TWC) have been put into focus due to their low-cost and high-efficient aftertreatment system. In this paper, the ammonia and nitrous oxide emissions during both steady-state and transient test cycles are analyzed with the aid of the regulated emission values and the temperatures in the TWC system. The results indicated that in the steady-state test cycle, NH3 are highest at low-speed high-load condition and N2 O emissions are at extremely low levels during the whole test cycle. At most operating modes of the steady-state test cycle, NH3 and N2 O emissions exhibit higher values when operated with high caloric value fuel. In both cold and hot start world harmonized transient cycle(WHTC) tests, motorway sub-cycle has the highest average NH3 emissions and adopting low caloric value fuel could reduce the tendency of NH3 formation; N2 O emissions are mainly generated in the engine starting period. In the cold start WHTC tests, adopting fuel with high caloric value is favorable for the abatement of N2 O emissions while in the hot start WHTC tests, using fuel with low caloric value would be a better choice for the control of N2 O emissions.